Composition and Biodegradation of DOM Leached from Permafrost End-members across the Western Canadian Arctic ... - MacDonald, Erin N. (University of Alberta Library, 2020)
Organic matter, upon dissolution into the aqueous state as dissolved organic matter (DOM), can undergo mineralization by microbes (biodegradation). There has been increasing effort to characterize DOM released from thawing permafrost because it may perpetuate a permafrost carbon feedback. Permafrost-derived DOM has a composition that can be highly susceptible to biodegradation (biolabile), but studies to date have been limited in scope. Importantly, diversity in deposit type and thaw modification processes have led to spatial and stratigraphic variability in permafrost, but our understanding of how the composition and biolability of DOM derived from differing permafrost types (end-members) is poor. Furthermore, few studies couple biolability measurements with assessing the microbial community structure, despite the important role that these microbes play in degrading DOM. This project aims to investigate how the composition of DOM leached from diverse permafrost end-members may vary, how compositional ...